The mediating role of positive emotion in the influence of store atmosphere and price discount on impulse buying among hypermart customers in Indonesia - Wardana, Rizky Hady; Barkah, Barkah; Purmono, Bintoro Bagus; Fauzan, Rizky; Yakin, Ikram (SEAN Institute, 2024)
This research examines the impact of store atmosphere and price discounts on impulse buying among consumers of Hypermart Department Store in Indonesia, with positive emotion as the mediating variable. The study used a quantitative research approach and used a purposive sampling to choose 260 participants. The data was collected through an online survey that underwent extensive testing to verify its legitimacy and dependability. Data analysis was conducted utilizing Structural Equation Modeling (SEM) methodology facilitated by the AMOS 24 program. The findings of this study demonstrate a positive and significant correlation between the store atmosphere and price discounts concerning impulse buying among consumers of Hypermart Department Store in Indonesia. In addition, this study has shown that positive emotion is a mediating factor in the association between store atmosphere, price discounts, and impulse buying. These findings can provide valuable insight for Hypermart Department Store management in designing more effective marketing strategies. This research implies that it can help companies increase their sales and profits through better management of store atmosphere and pricing strategies.